Pengaruh faktor teknologi terhadap hubungan antara faktor organisasi dengan penerimaan media sosial dalam pemasaran penginapan bajet - Noraihan, Mohamad (2014)
Social media has been accepted as a new marketing medium for survival of various industries in Malaysia, especially in budget accommodation. However, its adoption among small and medium enterprises in the tourism industry is still at the initial stage. Previous studies showed that organization’s internal and external factors determine the success of budget accommodation marketing, yet technological factor was less emphasized. Accordingly, this study was conducted to identify the influence of the organization’s internal and external factors, and the technological factor on the adoption of social media in the budget accommodation marketing. The theoretical framework of this study was developed by combining the Technology Acceptance Model (TAM) and Innovation Diffusion Theory (IDT). The method used in this study was cross-sectional survey involving budget accommodation operators in Kedah, Perlis and Penang. A total of 112 respondents answered the questionnaires and the data were analyzed by using multivariate techniques of Structural Equation Modeling. Path Analysis showed that a large variance in the adoption of social media in the budget accommodation marketing was contributed by the organization’s internal factor, external factor and technological factor by 71.6 percent. The findings also revealed that organization’s external factor and technological factor have significant direct influences towards the social media adoption. Technological factor was also found to be significantly mediating the relationship between organization factors and social media adoption. This study contributes to the application of TAM and IDT in the context of adoption of social media for budget accommodation marketing, as well as a guide to the operators as a new marketing strategy in the current tourism sector.